DETERMINANTS OF BUDGET TRANSPARENCY TOWARD FINANCIAL SUSTAINABILITY - Trisna T.B.; Diswandi; Nugraha A.P. I N. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
This research was conducted to examine the effect of the independence ratio and leverage on the transparency of regional budget management and the influence of independence, leverage, and transparency on regional financial sustainability. Based on sample purposive sampling found 34 local government districts and cities in Indonesia and analyzed by SEM-PLS technique. On average, the level of transparency in regional budget management in Indonesia is quite high, namely 78 percent of the total items that must be disclosed. While the test results show only leverage has a positive and significant effect on financial sustainability while regional self-reliance does not affect the transparency of budget management and financial sustainability and regional independence as well as leverage do not affect the transparency of budget management. This finding is consistent with the Neo-Institutionalism theory which states that organizations respond to pressure from their institutional context, where the research sample is district and city governments during the COVID-19 pandemic (2020-2021) that have national economic recovery program loans (PEN) from the central government so that the focus of the district and city governments is not on the transparency of regional financial management but on economic growth.